Prevalence of Vitamin-D Deficiency and its Associations with Skin Color In First Trimester Pregnant Women - Farina Zameer, Quratulain Memon, Ferrukh Zehravi, Sumaiya Aziz, Nazia Mushtaq, Naeem Ahmed Soomro, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Background and Aim: Vitamin D deficiency during pregnancy has negative clinical consequences, such as associations with glucose intolerance, pre-eclampsia, preterm birth and intra-uterine growth retardation. The rate of vitamin D deficiency in first trimester pregnant women differed depending on their skin colour. Objective: The present study aimed to determine the prevalence of vitamin-D deficiency and its association with skin color in first trimester pregnant women, at a tertiary care hospital in Karachi. Methodology: This descriptive cross-sectional study was carried out on 156 vitamin-D deficient first trimester pregnant women at Derma Clinic, Fatimiyah Hospital, Karachi from during the period from July 2021 to March 2022. Ethical approval was taken from the hospital’s ethical committee. All the twin pregnancy women >18 years with parathyroid history, chronic malabsorption, HIV, liver disease, and suspected drug use were excluded. Vitamin-D deficiency was referred to as <20 ng/mL against sufficient >20 ng/mL. Written informed consent was taken from each individual. During routine examination of pregnancy, approximately 10 mL blood sample was collected and centrifuged. Serum was extracted and analyzed for vitamin-D deficiency. SPSS version 25 was utilized for data analysis. Results: The overall mean age in vitamin D sufficiency and deficiency was 30.45 and 28.91 years respectively. The incidence of vitamin D deficiency was 53.8% (n=84). Of the total, about 72 (46.2%) pregnant women were vitamin D sufficient. The mean serum concentration (25- hydroxyvitamin D) was 25.9 ng/mL (95% CI, 24.5-27.5) in vitamin-D sufficient group and 10.7 ng/mL (95% CI, 9.5-11.5) in vitamin-D deficient group women. Deficiency in Vitamin-D was significantly found in dark-skinned women compared to light-skinned women (OR 2.56; 95% CI 1.1-6.35) based on the most parsimonious model when adjusted for vitamin D supplement, age, smoking, BMI, and parity. Conclusion: The present study found that the prevalence of vitamin D deficiency in pregnant women was 53.5%. The differences in prevalence and 25-OH vitamin D levels mainly rely on maternal skin color, highlighting the need for supplementation programs and consequent screening for pregnant women particularly, dark-skinned pregnant women. Keywords: Vitamin D deficiency, Skin Color, First Trimester, Pregnant women